Low Surface Expression of B7-1 (CD80) Is an Immunoescape Mechanism of Colon Carcinoma - Tirapu, Iñigo; Huarte, Eduardo; Guiducci, Cristiana; Arina, Ainhoa; Zaratiegui, Mikel; Murillo, Oihana; Gonzalez, Alvaro; Berasain, Carmen; Berraondo, Pedro; Fortes, Puri; Prieto, Jesús; Colombo, Mario P.; et al. (Cancer research (Chicago, Ill.), 2006)
Artificially enforced expression of CD80 (B7-1) and CD86 (B7-2) on tumor cells renders them more immunogenic by triggering the CD28 receptor on T cells. The enigma is that such B7s interact with much higher affinity with CTLA-4 (CD152), an inhibitory receptor expressed by activated T cells. We show that unmutated CD80 is spontaneously expressed at low levels by mouse colon carcinoma cell lines and other transplantable tumor cell lines of various tissue origins. Silencing of CD80 by interfering RNA led to loss of tumorigenicity of CT26 colon carcinoma in immunocompetent mice, but not in immunodeficient Rag−/− mice. CT26 tumor cells bind CTLA-4Ig, but much more faintly with a similar CD28Ig chimeric protein, thus providing an explanation for the dominant inhibitory effects on tumor immunity displayed by CD80 at that expression level. Interestingly, CD80-negative tumor cell lines such as MC38 colon carcinoma and B16 melanoma express CD80 at dim levels during in vivo growth in syngeneic mice. Therefore, low CD80 surface expression seems to give an advantage to cancer cells against the immune system. Our findings are similar with the inhibitory role described for the dim CD80 expression on immature dendritic cells, providing an explanation for the low levels of CD80 expression described in various human malignancies. (Cancer Res 2006; 66(4): 2442-50)